Kontribusi Motivasi Belajar terhadap Kepuasan Belajar Mahasiswa pada Mata Kuliah Pemrograman Web - Irsyadunas, Irsyadunas (Jurnal Riset Fisika Edukasi dan Sains, 2020)
This research is motivated by the unfulfilled learning satisfaction of ITP Informatics Department students. This type of research is correlational research. The purpose of this study is to find out anything that contributes to learning motivation towards student satisfaction. The study population was 146 people and a sample of 59 students of the ITP Informatics Department. The sampling technique was carried out by using the Non Probability Sampling Design technique, namely the incidental sampling technique. Sampling is taking the sample by chance, that is, by chance, by chance meeting with the researcher can be used as a sample if it happens that the person who happens to be found is suitable as the data source. Meanwhile, the data on learning motivation and learning satisfaction were collected through a questionnaire sent to students using a Likert scale that had been tested for validity and reliability. The results showed that learning motivation contributed significantly to the learning satisfaction of ITP Informatics Study Program students. amounted to 17.47. So it can be denied that Learning Motivation Contributes to ITP Informatics Department Student Learning Satisfaction.Depdikbud. (2003). Undang-undang RI NO.20 Tahun 2003 tentang Sistem Pendidikan Nasional. Jakarta: Lemhanas.Hamzah B. Uno. (2011). Teori Motivasi dan Pengukurannya: Analisis di Bidang            Pendidikan. Jakarta: Bumi aksara. Hamzah B Uno. (2007). Teori Motivasi dan Pengukurannya : Analisis di Bidang Pendidikan, Jakarta: Bumi Aksara.Siagian, Sondang P (2004). Teori motivasi dan aplikasinya. Jakarta: Rineka CiptaSargent, T (1999). The Conquest of American Inflation, Princeton University Press Suharsimi Arikunto. (2002). Prosedur Penelitian. Jakarta : Rineka Cipta.Suharsimi Arikunto. (2010). Prosedur penelitian : Suatu Pendekatan Praktik. (Edisi. Revisi). Jakarta : PT. Rineka Cipta.Slameto. (2010). Belajar dan Faktor-faktor Yang Mempengaruhinya. Jakarta: Rineka Cipta.Sugiyono, (2013). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.